Stainless Steel Crown pada Perawatan Pendahuluan Gigi Molar Pertama Permanen Muda: Keunggulan versus Kekurangan - Warizky, Nanda T.; Jeffrey, Jeffrey (Universitas Sam Ratulangi, 2025)
Abstract: Stainless steel crown (SSC) is a type of crown made from a dental alloy or stainless steel anatomically shaped and easily adaptable to extensively damaged teeth. This SSC can be utilized not only for deciduous teeth but also for young permanent teeth. This literature review aimed to further discuss the role of SSC as a preliminary treatment for young permanent first molars. Data search was conducted on electronic databases such as Google Scholar, NCBI (Pubmed), and Science Direct using the keywords